Nutritional characteristics and in vitro digestibility of silages from different corn cultivars harvested at two cutting heights - Caetano, Hamilton [UNESP]; Oliveira, M.D.S. [UNESP]; Freitas Júnior, J.E.; Rêgo, A.C.; Carvalho, M.V.; Rennó, F.P. (Sociedade Brasileira de Zootecnia, 2011)
Objetivou-se neste estudo avaliar as características nutricionais e a digestibilidade in vitro de silagens de diferentes cultivares de milho colhidas em duas alturas de corte. Foram avaliadas 11 cultivares (Dina 766, Dina 657, Dina 1000, P 3021, P 3041, C 805, C 333, AG 5011, FO 01, Dina co 9621 e BR 205) colhidas 5 cm acima do solo (baixa) e 5 cm abaixo da inserção da primeira espiga (alta). O experimento foi delineado em blocos casualizados (três blocos), arranjados em esquema fatorial 11 × 2. As silagens das plantas colhidas na altura de corte alta apresentaram teor médio de matéria seca significativamente superior às silagens das plantas colhidas na altura de corte baixa. As cultivares FO 01, AG 5011, Dina co 9621 e Dina 766 apresentaram maior teor de proteína bruta, que as cultivares C 805, P 3041 e P 3021, as quais apresentaram os menores teores deste nutriente. A elevação da altura de corte aumentou os coeficientes de digestibilidade verdadeira in vitro da matéria seca e digestibilidade in vitro da matéria seca das silagens avaliadas. O aumento da altura de corte melhorou o valor nutritivo das silagens, diminuindo as concentrações das frações fibrosas e aumentando a digestibilidade in vitro da matéria seca.

The objective of this study was to evaluate the nutritional traits and in vitro digestibility of silages from different corn cultivars harvested at two cutting heights. It was evaluated 11 cultivars (Dina 766, Dina 657, Dina 1000, P 3021, P 3041, C 805, C 333, AG 5011, FO 01, Dina co 9621 and BR 205) harvest 5 cm above ground (low) and 5 cm below the intersection of the first ear (high). It was used a random block design (three blocks), arranged in a 11 × 2 factorial scheme. Silages from plants harvested at high cutting height presented average content of dry matter significantly superior to silages from plants harvested at low height. Cultivars FO 01, AG 5011, Dina co 9621 and Dina 766 presented greater content of crude protein than cultivars C 805, P 3041 and P 3021, which presented the lowest contents of this nutrient. The raise in the cut height increased in vitro dry matter true digestibility coefficients and in vitro dry matter digestibility of silage evaluated. The increase in cut height improved nutritive value of silages by decreasing concentrations of fibrous fractions and increasing in vitro dry matter digestibility.
Características nutricionais e digestibilidade in vitro de silagens de diferentes cultivares de milho colhidos em duas alturas de corte
Keywords: composição bromatológica; cultivares de milho; digestibilidade in vitro; silagem; chemical composition; corn cultivars; in vitro digestibility; silage